2003
DOI: 10.1029/2001wr001260
|View full text |Cite
|
Sign up to set email alerts
|

Influences of the stream groundwater hydrology on nitrate concentration in unsaturated riparian area bounded by an intermittent Mediterranean stream

Abstract: [1] Stream aquifer hydrology and nitrate removal were studied, over a period of 2 years, in an unsaturated riparian zone, bounded by an intermittent Mediterranean stream, (Fuirosos, northeastern Spain). The riparian groundwater system is characterized by drastic hydrological changes and by mixing of stream water with hillslope groundwater. The hillslope groundwater flowed through a medium with low hydraulic conductivity (9.6 10 À3 < k s < 0.1 m d À1 ) and low specific discharges (1.7 10 À3 < q hll < 15 10). In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
114
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 106 publications
(125 citation statements)
references
References 43 publications
11
114
0
Order By: Relevance
“…Stream-to-aquifer fluxes at the valley bottom were attributed to differences in the hydraulic head between the aquifer and stream surface water, a process favoured by the high hydraulic conductivity of the alluvial sediments (5-20 m day −1 ; Butturini et al, 2003). Similar results have been reported for other alluvial streams in semiarid regions worldwide (Triska et al, 1993;Morrice et al, 1997).…”
Section: Influence Of the Alluvial Riparian Zone On Stream Water Exportsupporting
confidence: 75%
See 1 more Smart Citation
“…Stream-to-aquifer fluxes at the valley bottom were attributed to differences in the hydraulic head between the aquifer and stream surface water, a process favoured by the high hydraulic conductivity of the alluvial sediments (5-20 m day −1 ; Butturini et al, 2003). Similar results have been reported for other alluvial streams in semiarid regions worldwide (Triska et al, 1993;Morrice et al, 1997).…”
Section: Influence Of the Alluvial Riparian Zone On Stream Water Exportsupporting
confidence: 75%
“…However, Butturini et al (2003) reported a marked increase, rather than a decrease, in NO − 3 concentration at the FSW riparian groundwater during hydrological transitions due to the dissolution of salt buildup in the riparian soil during the dry period. This phenomenon has also been documented in other arid and semiarid regions (Heffernan and Sponseller, 2004;Meixner et al, 2007).…”
Section: Hydrological and Biogeochemical Solute Retention In The Allumentioning
confidence: 99%
“…Over the last decades in the semiarid Mediterranean environment, high external inputs of nitrate and irrigation in intensively managed agricultural systems reduced surface and subsurface water quality (Butturini et al, 2003;Lassaletta et al, 2009). In particular, vineyard soils are conventionally managed and frequently tilled, which reduces the vegetation cover and increases the proportion of bared soil.…”
Section: Introductionmentioning
confidence: 99%
“…This specific behaviour of the riparian soil allowed to easily accumulating nitrate that could be washed away by the interflow derived from the hillslope causing significant increase in nitrate streamwater concentrations. Butturini et al (2003) previously pointed out the unsaturated riparian soil layer at Fuirosos as a possible source of nitrate. In this study, it was observed that the rise of the local riparian groundwater table, after the summer drought, resulted in the rapid flushing of nitrate stored in the soil during the long dry period.…”
Section: Discussionmentioning
confidence: 99%
“…Bernal et al (2007) suggested that Mediterranean riparian soils act as source or sink of dissolved nitrogen depending on the period of the year, mainly due to contrasting soil moisture condition between the dry and the wet period. Moreover, Butturini et al (2003) suggested the unsaturated riparian soil of the Fuirosos catchment, a small intermittent Mediterranean stream in Catalonia (Spain), as a possible source of nitrate, especially after the summer drought, which can be rapidly mobilized due to the formation of a rising riparian groundwater table into the unsaturated upper soil layer adjacent to the stream channel. The nitrogen dynamics of the Fuirosos catchment were analysed previously with the process-based Integrated Catchment Model of Nitrogen (INCA-N) model (Whitehead et al, 1998;Wade et al, 2002;Bernal et al, 2004).…”
Section: Introductionmentioning
confidence: 99%